2010
DOI: 10.1586/epr.10.6
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of the glia secretome and the CSF proteome: neuroinflammation and novel biomarkers

Abstract: Glial cells in the CNS are likely to communicate with other glial cells and neurons through secreted proteins. Glia-derived proteins also participate in neuroinflammation, which is a major component of neurodegenerative disease. Cerebrospinal fluid (CSF) is the biological fluid that best reflects the physiological or pathological conditions of the CNS. Proteins secreted from glial cells are often detected in the CSF. One of the major cellular sources of the highly abundant CSF proteins is glia. Combined analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 116 publications
0
16
0
Order By: Relevance
“…We and others have previously investigated the secretome of brain glial cells [3,4,6,7,51,65,66]. Proteins secreted from glial cells have been shown to regulate neuron–glia communication and to play important roles in interglial interactions [67]. In the present study, we identified PAI-1 as the major secreted protein of glia through LC-MS/MS analysis of mouse mixed glial cultures.…”
Section: Resultsmentioning
confidence: 71%
“…We and others have previously investigated the secretome of brain glial cells [3,4,6,7,51,65,66]. Proteins secreted from glial cells have been shown to regulate neuron–glia communication and to play important roles in interglial interactions [67]. In the present study, we identified PAI-1 as the major secreted protein of glia through LC-MS/MS analysis of mouse mixed glial cultures.…”
Section: Resultsmentioning
confidence: 71%
“…Proteins secreted from glial cells play an important role in the intercellular communication among cells in the central nervous system and contribute to proteome of cerebrospinal fluid. Astrocytes secrete numerous inflammatory mediators that are associated with tissue injury, inflammation and the pathogenesis of neurodegenerative disease such as Alzheimer's disease and Parkinson's disease [52]. Astrocyte secretome under normal or proinflammatory conditions have been partially mapped in primary cultures of astrocytes of mouse and rat origin.…”
Section: Astrocytes and Neural Progenitor Cellsmentioning
confidence: 99%
“…However, challenges were encountered during analysis including dynamic range (affecting detection of low abundance biomarkers), difficulty assessing the relative contribution of a specific tissue to the proteome of a specific body fluid and the possibility of contamination by blood. To circumvent some of these confounding backgrounds when studying body fluids to mine for tissue-specific biomarkers, one can compare the proteome of a given body fluid with the secretome of cells originating from the tissue in proximity to this body fluid, such as previously documented in a combined analysis of the secretome of glial cells and the cerebrospinal fluid proteome [67]. …”
Section: In Vivo Secretome Profilingmentioning
confidence: 99%